Determination of Lead (II) Ion From Industrial Waste Content Of" Olmaliq Kmk " Jsc In The SorbtsionPhotometric Method (Eurasian Research Bulletin, 2023)
The organic reagent 1,3,4-thiadiazole-2,5-ditiol is used as an analytical reagent for the lead (II) ion. The possibility of their application as a specific analytical reagent has been developed for immobilization in fiber carriers and detection of metal ions, specifically lead (II) ion detection. a simple, Express method of detecting a lead (II) ion using a 1,3,4-thiadiazole-2,5-ditiol organic reagent has been demonstrated. The Reagent reacts with the lead (II) ion in a 1:6 ratio